1999
DOI: 10.2116/analsci.15.785
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Aromatic Isomers by Capillary Gas Chromatography with Two Calix[4]arene Polysiloxane Stationary Phases

Abstract: Two new stationary phases, cone bis(undecenyloxy)-p-t-butyl calix [4]crown-5 polysiloxanes (PSO-C-c[4]c-5) and partial cone 5,11,17,23-t-butyl-25,27-diethoxy-26,28-diundecenyl calix[4]arene polysiloxane (PSO-PC-c[4]E), are synthesized and used as stationary phases in capillary column gas chromatography. Their chromatographic characteristics, such as column efficiency, capacity factor, average polarity, operation temperature range, and peak asymmetry were measured. Their column efficiency is over 3000 plates m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
(8 reference statements)
1
9
1
2
Order By: Relevance
“…As calixcrowns possess well-preorganized structures and more rigid binding sites in comparison with calixarenes and crown ethers, they exhibited superior recognition ability, specially, the complexation selectivity toward cations [1,2]. With the extensive and in-depth studies of all kinds of calixcrowns, more and more attentions are paid to calixcrown-based polymers which may be processed into materials with potential applied perspective on ion exchange and adsorption [3], gas chromatogram [4], ion chromatogram [5], etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As calixcrowns possess well-preorganized structures and more rigid binding sites in comparison with calixarenes and crown ethers, they exhibited superior recognition ability, specially, the complexation selectivity toward cations [1,2]. With the extensive and in-depth studies of all kinds of calixcrowns, more and more attentions are paid to calixcrown-based polymers which may be processed into materials with potential applied perspective on ion exchange and adsorption [3], gas chromatogram [4], ion chromatogram [5], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In 1995, Zhong et al [6] first reported the synthesis and properties of the calix [4]crown sioxane polymer. Arena reported the utility of calix [4] silica gel for the separation of Na + and Cs + in liquid chromatography [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] In Kieselgel eingeschlossene Cavitanden wurden für Umweltüberwachung [40] und Chromatographie eingesetzt. [41] In den frühen 90er Jahren haben Shinkai und Mitarbeiter [42,43] [45][46][47] wird eine Vielzahl von möglichen Wirt-Gast-Elementen für solche supramolekularen Polymere aufgezeigt (Abbildung 1).…”
Section: Introductionunclassified
“…Since calixarene has a special cavity structure, high melting point and thermal stability, it was found to be useful in gas chromatography (GC) as stationary phase. Mangia et al [2] first reported in 1983 the separation of homologues of alcohol, chlorinated hydrocarbons and aromatics on a column packed with calix [8]arene supported on silanized Chromosorb W. Feltl et al [3,4] further reported the inclusion properties of unsubstituted calixarenes in gas chromatography, but, as the result of low column efficiency, their utility in GC is limited. Our group have synthesized several lowerrim modified calix [4]arene derivatives and evaluated their gas chromatographic properties.…”
Section: Introductionmentioning
confidence: 99%